Experimental Investigations of the Turbulence Impact on the performance of the HAWT - Al-Abadi, Ali Kedher Kashin; Seok, Julie; Härtl, Michael; Ertunc, Ozgur; Delgado, Antonio (10th PhD Seminar on Wind Energy in Europe, 2014)
The present study aims at highlighting the influence of the turbulence on the performance of the HAWT. For the investigation, we have designed a laboratory-scale HAWT that can efficiently perform in the LSTM wind tunnel. Thus, the obtained results are reliable and possible to be reflected and evaluated for different scales of HAWTs. The turbine has been exposed to turbulence with various energy and length scale contents. The turbulence is generated by two static squared mesh grids. Hence, two mainly different turbulence scales are obtained. In addition, the distance between the wind-turbine and the grid is adjusted to have additional sub-turbulence scales for each grid. The developments of turbulence at different scales in the flow direction at various Reynolds numbers are measured. Furthermore, up and down-stream turbulence intensities (TI) distributions are measured to give insight on the surrounding-wake interaction. Performance measurements are conducted with and without turbulence, and winglet is used to isolate the tip vortex effect. The study shows that the higher the turbulence, the more power can be extracted by the turbine. The turbulence helps in damping tip vortices and, thus, reduces turbine tip losses. In addition, it contributes in suppressing the boundary layer and preventing the separation that, in turn, enhances the HAWT performance. <br